2020
DOI: 10.34172/ijhpm.2020.224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Participation of Community Pharmacists in Primary Healthcare Services in Nigeria: A Mixed-Method Survey

Abstract: Background: Achieving universal health coverage in poorly-resourced settings like Nigeria demands optimal mobilization of all healthcare resources including community pharmacists. Such efforts are hampered by insufficient data on primary healthcare (PHC) contributions by community pharmacists. The study aimed to identify PHC services offered by community pharmacists; assess impact of technologies on PHC service quality; and evaluate factors influencing management of PHC services in Nigeria. Methods: A descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 29 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…[17] This is crucial considering the expanded roles of the community pharmacist (CP) as a first-line healthcare workforce in primary healthcare delivery. [18] In this study, educational qualifications have been shown to have minimal impact on buying decisions. [12,16,19] The study utilized structural equation modeling techniques to examine the impact of gender, location of the business, and type of business model on decision-making on CP in selected cities in South West, Nigeria.…”
Section: Path Analysis Of Study Variables Using Spss Amosmentioning
confidence: 79%
“…[17] This is crucial considering the expanded roles of the community pharmacist (CP) as a first-line healthcare workforce in primary healthcare delivery. [18] In this study, educational qualifications have been shown to have minimal impact on buying decisions. [12,16,19] The study utilized structural equation modeling techniques to examine the impact of gender, location of the business, and type of business model on decision-making on CP in selected cities in South West, Nigeria.…”
Section: Path Analysis Of Study Variables Using Spss Amosmentioning
confidence: 79%
“…For example in Nigeria, CPs have been rendering primary healthcare with extended roles in chronic disease management, public health, and health promotion unofficially. 78 , 79 In Malaysia, despite the lack of a legal framework for primary care roles, CPs offer health screenings and chronic diseases services to the general public. 80 , 81 , 82 , 83 In Jordan, there is a lack of legal backing for pharmacist's primary care role 84 despite evidence that clinical pharmacy and medication therapy management services in hospitals and community pharmacies improved patient health outcomes.…”
Section: A Snapshot Of Community Pharmacists' Involvement In Chronic ...mentioning
confidence: 99%
“…Most community pharmacies in Nigeria are independently owned and operated by licensed pharmacists [ 4 ]. Community pharmacists are easily accessible and trusted frontline healthcare professionals who provide pharmaceutical care to the community [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most community pharmacies in Nigeria are independently owned and operated by licensed pharmacists [ 4 ]. Community pharmacists are easily accessible and trusted frontline healthcare professionals who provide pharmaceutical care to the community [ 4 ]. Moreover, it costs less to receive health services in community pharmacies than in Nigerian hospitals due to free consultation and counselling [ 5 ].…”
Section: Introductionmentioning
confidence: 99%